Renewable and Nonrenewable Energy Consumption, Government Expenditure, Institution Quality, Financial Development, Trade Openness, and Sustainable Development in Latin America and Caribbean Emerging Market and Developing Economies - Le, Hoang Phong; Bao, Ho Hoang Gia (International Journal of Energy Economics and Policy, 2019)
This study investigates the role of non-renewable and renewable energy consumption in the sustainable development in 16 Latin America and Caribbean Emerging Market and Developing Economies (EMDEs) incorporating capital, government expenditure, institution quality, financial development, and trade openness by a multivariate framework using annual data from 1990 to 2014. We apply second-generation techniques for heterogeneous panel data as the presence of cross-sectional dependence and slope heterogeneity is detected. Accordingly, CADF and CIPS unit root tests show that all variables are integrated at order 1. Westerlund cointegration test acknowledges the long-run relationship among the variables. The long-run estimation is conducted by the Augmented Mean Group (AMG), Mean Group (MG) and Common Correlated Effects Mean Group (CCEMG) estimators. The findings indicate that, in the long run, renewable and non-renewable energy use, along with other factors including government expenditure, gross fixed capital formation, trade openness and financial development, positively affects the economic growth in the selected countries. The empirical results imply that the EMDEs in Latin America and the Caribbean should appropriately implement fiscal policies for macroeconomic stabilization in combination with finance and international trade policies as well as effective energy strategies to attain their sustainable development objectives. Keywords: Sustainable Development; Renewable and non-renewable energy use; Heterogeneous Panel Data; Economic growth; Emerging Market and Developing Economies; Latin America and the Caribbean. JEL Classifications: C01; E02; H72; O11; Q01; Q43 DOI: https://doi.org/10.32479/ijeep.8506